Laboratory Equipment for Ozone Techniques Application in Biology and Medicine - Zinchenko, V. D.; Golota, V. I.; Sukhomlin, E. A.; Taran, G. V.; Belykh, I. A. (Problems of Cryobiology and Cryomedicine, 2005)
There has been described an ozone generator for medical and biological experiments using ozone technologies and the chamber for different objects treatment with ozonized solutions and ultrasound. In ozone generator a barrier-free discharge tube is applied, which is perfectly operating at an increased humidity of gas passing through. While working with pure oxygen the generator provides ozone concentration in ozone-oxygen mixture of up to 20 mg/ml, when working with air this index makes up to 8mg/l. Value of gas flow through a discharge tube is 0.1 to 6 l/min. The equipment can be used for ozone saturation of a number of solutions, in the experiments on studying the stimulating effect of ozone low doses on biological objects and for various objects sterilization using its high doses. Application of the equipment described is illustrated by the experiment of microorganismsâ€™ growth stimulation by low doses of ozone. Â 